The Financial Burden of Disability: Narratives of Filipino Families with Low Socioeconomic Status Raising Children with Disabilities - Bondad, Olivia Cassandra P.; Ancho, Inero V.; Bailey, Rhea R.; Ferido, Melissa P.; Pelegrina, Daisy V. (Indonesian Journal of Community and Special Needs Education, 2024)
Raising a child with a disability (CWD) often incurs additional costs for any family. However, when a family is situated within a low socioeconomic status, the financial burden can be even more pronounced. This prompted a phenomenological study to delve deeper into the lived experiences of such families, focusing on how disability exacerbates the family’s finances. Utilizing semi-structured interviews, participants were able to narrate the unique challenges and barriers they faced in raising CWD within the context of limited financial resources. The emerging themes revealed multifaceted challenges, including caregiving tasks, parental stress, and hurtful remarks. Concerns about the future of the children and the caregiving responsibilities being placed on mothers were also highlighted. Additionally, families often face trade-offs between meeting the needs of other family members and those of the CWD due to financial constraints. Access to healthcare presents further barriers, particularly for low-income families. While some existing support programs offer relief, there is a notable absence of specific support for CWD families. The Head, meanwhile, also shared his plans for the person with the disability community.